Ocular adverse events in PD-1 and PD-L1 inhibitors - James Murray; Howard Streicher; Elad Sharon; LeAnne Young; Shanda Finnigan; H Nida Sen; Helen X Chen (Journal for ImmunoTherapy of Cancer)
Background Programmed death-1 (PD-1) and programmed death-ligand 1 (PD-L1) inhibitors can cause unique immune-related adverse effects due to non-specific immunological activation. However, less is known about adverse effects of these drugs in the eye.Methods Two adverse event databases were retrospectively reviewed. The two databases consisted of a routine adverse event database and a serious adverse event database of expeditiously submitted reports. Patients with any malignancy who had ocular adverse events while on PD-1/PD-L1 inhibitor treatment were included. Patients received nivolumab, pembrolizumab, atezolizumab or durvalumab alone or in combination with other anticancer agents per each trial’s protocol. Databases were queried up to May 19, 2020.Results In the routine adverse event database, 272 adverse events from 213 patients were reported and in the serious adverse event reporting database, 59 ocular adverse events from 47 patients were reported. A lower estimate of the prevalance from the routine adverse event database showed 259/7727 patients on study treatment arms reporting ocular adverse events (3.3% prevalence). Excluding trials that do not report lower grade adverse events to the routine adverse event database results in a higher end estimate of 242/3255 patients on study treatment arms reporting ocular adverse events (7.4% prevalence). Ocular events occurred early after drug initiation (routine database: median 6 weeks, IQR 0–16, serious adverse events database: median 11 weeks, IQR 6–21). The median Common Terminology Criteria for Adverse Events grade was grade 1 (mild) (IQR 1–2) and grade 2 (moderate) (IQR 2–3) for the routine database and the serious adverse events database, respectively. In-depth analysis of the serious adverse event reports revealed varying degrees of clinical workup, with 30/47 patients (64%) receiving ophthalmological evaluation and 16/47 (34%) of patients having to delay or discontinue treatment. However, 16/47 (34%) patients experienced resolution and 14/47 (30%) patients experienced at least some improvement.Conclusions This is one of the largest analyses of ocular adverse events in patients treated with PD-1/PD-L1 inhibitors in the USA. We found ocular adverse events are rare complications of PD-1/PD-L1 inhibitor therapy, can be severe enough to cause treatment discontinuation/delay, and may not always be appropriately evaluated by eye specialists. Standardized plans for ophthalmology evaluation and management of ocular toxicities are needed in studies of patients treated with PD-1/PD-L1 inhibitors.